Transfemoral venous approach for Onyx embolization of anterior fossa dural arteriovenous fistulae. (23rd March 2013) - Spiotta, Alejandro M; Hawk, Harris; Kellogg, Ryan T; Turner, Raymond D; Chaudry, M Imran; Turk, Aquilla S
Abstract : Background: Dural arteriovenous fistulae (dAVF) of the anterior fossa have a malignant course since they exclusively drain into cortical frontal veins and warrant aggressive treatment. Classically, these lesions have been treated with microsurgical clipping of the fistulous connection. We describe a transvenous approach for Onyx embolization of these lesions that relies on distal venous access using a flexible new-generation guide catheter. Methods: A retrospective review was performed of all patients with an anterior fossa dAVF treated at the Medical University of South Carolina since 2010. Charts, procedural records, angiographic images and follow-up were reviewed. Three patients were identified. Results: Transfemoral venous access and distal transvenous sinus access was obtained in a retrograde fashion to at least the level of the right transverse sinus. Once a distal guide catheter position was obtained within the venous sinus system, a microcatheter was advanced into the predominant draining anterior frontal cortical vein in preparation for embolization. Onyx 34 embolization was then initiated from this position with the objective of achieving penetration across the vascular shunt. Conclusions: Our experience demonstrates that transvenous Onyx embolization offers an effective and safe alternative to the classic neurosurgical treatment of anterior fossa dAVF.